Trauma and testimony in ferenczi: An analysis of voices from tchernóbil by svetlana aleksiévith - Baracat, Juliana [UNESP]; Abrão, Jorge Luis Ferreira [UNESP]; Martínez, Viviana Carola Velasco (FapUNIFESP (SciELO), 2020)
This article approaches the concepts of trauma and testimony as elaborated by Sándor Ferenczi and associates them to Svetlana Aleksiévitch’s book about the nuclear disaster of Chernobyl. It aims to show the value of Ferenczi’s observations on collective trauma by highlighting three topics: relational dissymmetry, process of denial and wounded narcissism. Aleksiévitch’s book allowed us to understand in what ways the author’s role resembles the one described by Ferenczi.
Trauma y testimonio en ferenczi: Una lectura de voces de chernóbil de svetlana aleksiévitch
Trauma et témoin chez ferenczi: Une lecture du livre la supplication de svetlana aleksiévitch
Keywords: Colective trauma; Denial; Ferenczi; Testimonial literature